Genotypic and phenotypic variations in methicillin-resistant Staphylococcus aureus isolates from outpatient, inpatient and nursing homes. Issue 3 (22nd January 2019) - Delorme, Thierry; Dang, Duyen; Garcia, Alexander; Nasr, Payman
Abstract : Purpose . The epidemiological shift in MRSA distribution from healthcare-related facilities to the general population is distressing and requires continuous monitoring to manage and control the rate of incidences. Method . The retrospective relationship between genetic and phenotypic variability of methicillin-resistant Staphylococcus aureus (MRSA) isolates was determined in respect to the specimen source, patient location, sex and age. A total of 521 MRSA isolates were classified based on SCCmec, mec, agr, pvl and spa genetic markers using three different multiplex PCRs. Results . Based on the genetic variability, the isolates were divided into 97 profiles, of which 59% belonged to only two profiles (P17 and P33). P17 was the predominate profile, harbouring SCCmecIVa, ccr2, mecB, agr1, spa413 and pvl markers. P17 was more prevalent among the younger population (average 33.9 years) from outpatient (77%) locations and wound (88%) sources. The second largest profile was P33, harbouring SCCmecII, ccr2+ccr3, mecA, agr2, spa413 and no PVL. P33 was more prevalent in the older population (average 70.7 years) and more common in females (62%) than males (38%). With respect to antibiotic resistance, P33 exhibited a high rate of resistance to penicillins, cephalosporins, fluoroquinolones and macrolides, and P17 had a lower resistance to fluoroquinolones. Conclusion . This report contributes to the existing understanding of evolutionary epidemiology of antibiotic resistance in MRSA. The diversity of MRSA isolates and unique environmental preferences for each profile highlights the importance of epidemiological knowledge of MRSA distribution to determine the best treatment for patients in both community and hospital settings.